Reconstruction of sound source signal by analytical passive TR in the environment with airflow. (31st March 2017) - Wei, Long; Li, Min; Yang, Debin; Niu, Feng; Zeng, Wu
Abstract: In the acoustic design of air vehicles, the time-domain signals of noise sources on the surface of air vehicles can serve as data support to reveal the noise source generation mechanism, analyze acoustic fatigue, and take measures for noise insulation and reduction. To rapidly reconstruct the time-domain sound source signals in an environment with flow, a method combining the analytical passive time reversal mirror (AP-TR) with a shear flow correction is proposed. In this method, the negative influence of flow on sound wave propagation is suppressed by the shear flow correction, obtaining the corrected acoustic propagation time delay and path. Those corrected time delay and path together with the microphone array signals are then submitted to the AP-TR, reconstructing more accurate sound source signals in the environment with airflow. As an analytical method, AP-TR offers a supplementary way in 3D space to reconstruct the signal of sound source in the environment with airflow instead of the numerical TR. Experiments on the reconstruction of the sound source signals of a pair of loud speakers are conducted in an anechoic wind tunnel with subsonic airflow to validate the effectiveness and priorities of the proposed method. Moreover the comparison by theorem and experiment result between the AP-TR and the time-domain beamforming in reconstructing the sound source signal is also discussed. Highlights: Sound source signal is reconstructed via AP-TR combined with shear flow correction. More accurate sound source signal can be obtained by AP-TR in environment with flow. AP-TR offers an alternative way to reconstruct sound source signals with airflow. Sound field measurement in a wind tunnel is conducted to prove the proposed method.